2003
DOI: 10.1002/bdra.10007
|View full text |Cite
|
Sign up to set email alerts
|

Are there teratogenic risks associated with antidotes used in the acute management of poisoned pregnant women?

Abstract: Despite the limited evidence supporting the risk of antidote use during pregnancy, antidotes should be used when there is a clear maternal indication to decrease the morbidity or mortality associated with poisoning. The only exception may be penicillamine, which is a teratogen. Better antidotes exist for most poisonings that penicillamine could potentially treat. At this time, there is no known fetal indication for all antidotes. Reporting the use of an antidote during pregnancy should be encouraged, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 91 publications
(79 reference statements)
0
18
0
4
Order By: Relevance
“…A systematic review on the teratogenicity of antidotes concluded that despite the limited supporting evidence, (1) Pyrethrins (1) Glyphosate (1) Unknown (1) The percentage represents the proportion of the total number of cases (n=103) in which the specific agent class and/or agent was reported. Respondents could report more than one agent and agent class for each case; therefore, percentages can add up to more than 100 APAP N-acetyl-p-aminophenol, ASA acetylsalicylic acid, NSAIDs non-steroidal anti-inflammatory drugs antidotes should be used when indicated to decrease maternal morbidity and mortality associated with poisoning despite potential fetal risks [18,19]. Acetaminophen crosses the placenta and is metabolized by fetal liver, where generation of the toxic metabolite (N-acetyl-p-benzoquinone imine) may occur [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on the teratogenicity of antidotes concluded that despite the limited supporting evidence, (1) Pyrethrins (1) Glyphosate (1) Unknown (1) The percentage represents the proportion of the total number of cases (n=103) in which the specific agent class and/or agent was reported. Respondents could report more than one agent and agent class for each case; therefore, percentages can add up to more than 100 APAP N-acetyl-p-aminophenol, ASA acetylsalicylic acid, NSAIDs non-steroidal anti-inflammatory drugs antidotes should be used when indicated to decrease maternal morbidity and mortality associated with poisoning despite potential fetal risks [18,19]. Acetaminophen crosses the placenta and is metabolized by fetal liver, where generation of the toxic metabolite (N-acetyl-p-benzoquinone imine) may occur [20].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about its teratogenic risk [18]. It is classified by the FDA as a pregnancy category C drug [27].…”
Section: Discussionmentioning
confidence: 99%
“…The management of organophosphate intoxication in a pregnant patient has been a matter of debate. Literature on the usage of atropine and pralidoxime during pregnancy is scanty (Karalliedde et al 1988;Tenenbein 1994;Bailey 2003) and is not part of the general therapeutic strategy (Okumara 1997). Since this middle-aged pregnant woman was finally carrying a viable baby after several miscarriages, no risks were taken.…”
Section: Discussionmentioning
confidence: 99%
“…while relevant parameters (clinical improvement and effects of atropine toxicity) were strictly monitored and further administration of atropine was discontinued at the first signs of hallucination. The decision to use pralidoxime was based on the limited literature available on its use in pregnancy (Tenenbein 1994;Bailey 1997Bailey & 2003, the fact that the pregnancy was well beyond the organogenesis and that the baby could be delivered if needed at any stage during the treatment. Moreover in order to obtain the most optimal outcome, pralidoxime has to be started as soon as the diagnosis is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…B. bei Methanolintoxikation ebenso beobachtet wie bei Überdosen von Paracetamol und Eisenpräparaten, die mit Antidota behandelt wurden. Zum Chelatbildner Dimercaprol, der dem bei uns gebräuchlichen DMPS (2,3-Dimercapto-1-propansulfonsäure) chemisch verwandt ist, liegen mehrere Fallberichte zur Anwendung bei Arsen-und Bleivergiftung vor, die keine Hinweise für ein embryotoxisches Risiko geben [2]. Antidotsubstanzen, die v. a. bei anderen Indikationen eingesetzt werden, wie z.…”
unclassified